Food Innovation and Local Social Movement: The Case of Juang Community of Lebak, Indonesia - Riswanda Riswanda; M. Dian Hikmawan; Bayu Nurrohman; Ika Arinia Indriyany; Yeby Ma’asan Mayrudin (Journal of Asian Social Science Research, 2022)
This article aims to describe how the movement carried out by the Juang Community of Lebak, Indonesia, encouraged and empowered the community to develop honey bee cultivation in Lebak Regency amidst the growing issue of local food innovation and diversification. This study contributes to the studies of the movement of honey bee cultivation, which are so far still understudied. Research on honey bees commonly focuses on collaboration with government or community empowerment. This study, however, tries to look at the social movements aimed at developing honey production in local contexts using a qualitative research method with a descriptive approach. The results show that the Juang Community of Lebak was a driving force for the community in Kampung Buana in cultivating honey bees. It attempted various activities such as building collaboration, strengthening and developing resources, and seeking wider networks for a more open market. However, the movement had difficulties in establishing good collaboration from various parties to jointly develop the potential of honey bees in Lebak Regency.